PENGENDALIAN KUALITAS PRODUK ORAL HEALTH CARE (OHC) PADA PT AMTEK ENGINEERING BATAM - Satria, Anggi; Arista, Anggia (Computer Science and Industrial Engineering, 2021)
The background of this research is based on the discovery of various defects in the production process so that companies need to take quality control measures to maintain the quality of their products, so that their products can be accepted by consumers. PT Amtek Engineering Batam is a manufacturing company that produces stators. The purpose of this study was to analyze quality control, types of defects and the factors causing stator defects. The data collection technique is done by interview, observation, product defect data, and stator total production data. The data is processed using the sqc method, namely check sheets, Pareto diagrams, P control charts, and fishbone diagrams. The results of data analysis using the P map, Over lapping defects and Gap defects are outside the upper control limits. Based on the Pareto diagram it can be concluded that the type of Over lapping defect is the highest with the number of 4,242 pcs or 48.2%, the type of Gap defect is 3,306 pcs or 37.6% and Scratched defect is 1,256 pcs or 14, 2%. Based on the fishbone diagram, it is found that machine factors are the main cause of product defects.